The Influence of Managerial Ability, CFO Tenure, and Executive Compensation on Accounting Conservatism - Almi Hafiz; Erwin Saraswati; Arum Prastiwi (CV. Sakura Digital Nusantara, 2026)
This study aims to analyze the effect of managerial ability, Chief Financial Officer (CFO) tenure, and executive compensation on accounting conservatism. Accounting conservatism is considered one of the key principles in financial reporting, serving to enhance prudence and reduce managerial bias in the presentation of financial statements. Executive-related characteristics are believed to influence the application of conservatism, therefore this research focuses on managerial ability, tenure experience, and executive compensation. The research method employed is a quantitative approach using regression analysis. The data were processed with the assistance of SPSS software through classical assumption tests, descriptive analysis, and regression testing. The findings reveal that managerial ability has a positive and significant effect on accounting conservatism, while CFO tenure has a negative and insignificant effect. Meanwhile, executive compensation has a negative but significant effect on accounting conservatism. Thus, the results highlight that managerial ability is the most consistent factor in driving the implementation of accounting conservatism compared to tenure or executive compensation.